Investigation of Heavy Metals in the Persian Gulf Pearl Oyster Pinctada radiata by Using Atomic Absorption Spectroscopy - A. Behbahani; Gh. Aminiranjbar (‬‭Majallah-i ̒Ilmī-i Shīlāt-i Īrān, 1996)
Bioaccumulation of seven heavy metals (Zn, Cu, Fe, Cd, Pb, Ni, Mn) were determined in the Persian Gulf pearl oyster "Pinctada radiata" collected from major pearl oyster beds of Lavan and Handurabi Islands and Nakhiloo port during six months, winter of 1994 and spring of 1995, by spectroscopy, considering their environmental condition such as : salinity, pH, dissolved oxygen and transparency. Three ways analysis of variance and mean comparison tests, have been used to determine the relationship between concentration of metals and factors including time sampling, sites and size of samples...... References